The Influence of Intellectual Capital on Company Performance with Risk Management as a Mediating Variable in Private Commercial Bank Companies Listed on the Indonesian Stock Exchange - Mirtawati, Mirtawati; Laekkeng, Mursalim; Zakaria, Junaiddin (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
With risk management as a mediating variable, the aim of this research is to determine the impact of intellectual capital on company performance. The VAIC proxy is used to estimate intellectual capital, the BOPO proxy to estimate risk management, and the Return on Assets proxy to estimate company performance. The target population for this research is private commercial banks listed on the Indonesia Stock Exchange from 2018 to 2022. Nine private commercial banking institutions are the research sample. Path analysis was used in the data. The E-Views 12 program was used for data processing. The findings of this research show that 1) intellectual capital has a positive and significant impact on business performance. (2) Risk management is negatively and significantly influenced by intellectual capital. (3) Risk management can mediate the relationship between intellectual capital and company performance. (4) Risk management has a negative and significant effect on company performance.